1997
DOI: 10.1177/004728759703500401
|View full text |Cite
|
Sign up to set email alerts
|

The Loyal Traveler: Examining a Typology of Service Patronage

Abstract: The first goal of this study was to determine whether Day's (1969) measure of loyalty could be extended to better understand travel service patronage. Findings provide clear support that this composite measure, of repeat purchase and loyal attitude, is an effective approach to distinguishing the loyal traveler. A cluster analysis that combined scores on the composite measure from 428 travelers supported a two-dimensional matrix that identified four types of loyalty: true, spurious, latent, and low. This accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
153
0
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(165 citation statements)
references
References 26 publications
4
153
0
8
Order By: Relevance
“…Baloglu (2001), Pritchard and Howard (1997), and Rowley and Dawes (2000) have utilised cluster analysis of behavioural consistency and psy- chological attachment items to confirm the four quadrant structures proposed by Selin et al (1988) and Backman (1988). These studies have confirmed that four distinct types of loyalty exist in a multitude of settings.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Baloglu (2001), Pritchard and Howard (1997), and Rowley and Dawes (2000) have utilised cluster analysis of behavioural consistency and psy- chological attachment items to confirm the four quadrant structures proposed by Selin et al (1988) and Backman (1988). These studies have confirmed that four distinct types of loyalty exist in a multitude of settings.…”
Section: Literature Reviewmentioning
confidence: 90%
“…While empirical support for the typology has been noted in wider marketing literature (Dick and Basu, 1994), and leisure services (Selin et al 1988, Backman andCrompton 1991), hospitality researchers have further confirmed the application of four distinct types of loyalty in a multitude of settings (Baloglu, 2001;Pritchard and Howard, 1997 • Spurious/artificial loyalty customers are those who make frequent purchases yet are not emotionally attached to the brand. The high patronage level of spuriously loyal customers may be attributed to habitual buying, financial incentives, convenience, lack of alternatives, etc.…”
Section: Classifying Loyaltymentioning
confidence: 99%
“…However, this approach has been criticized by Dick and Basu (1994) as lacking a conceptual standpoint, and producing only the static outcome of a dynamic process. In addition, Pritchard and Howard (1997) also state that focusing on behavior alone cannot capture the reasons behind the purchases: repeat purchase may occur simply for arbitrary reasons such as price, time convenience and lack of choice, other than from any sense of loyalty or allegiance. Vol.…”
mentioning
confidence: 99%
“…Pendekatan ini mengkombinasikan dua dimensi sebelumnya, dan mengukur loyalitas melalui preferensi produk, propensitas alih merek, frekuensi pembelian, pembelian terakhir kali, dan jumlah total pembelian pelanggan (Pritchard & Howard, 1997;Hunter, 1998;Wong et al, 1999).…”
Section: Loyalitas Sikap (Attitudinal)unclassified